Journalism Can Establish its Credentials—All it Takes is a Little Research. (June 2015) - Tanner, Stephen
The critical difference between the academic and journalism research comes at the beginning. While the academic project is subject to scrutiny and approval by university-based ethics committees, the journalistic project is not subject to the same requirements. However, this should not serve to devalue the journalism relative to the academic alternative. For Journalism to establish its research credentials in academe it needs to do a better job at selling itself: at explaining not just what it does, but how it does it.